Mathematical simulation of heat and mass exchange processes during dissociation of gas hydrates in a porous medium - Dreus, A. Yu.; Bondarenko, V. I.; Biletskyi, V. S.; Lysenko, R. S. (Національний гірничий університет, 2020)
Purpose. The development of methodology of research and analysis of heat and mass exchange processes in a hydrate containing porous rock layer in case of a pressure drop at its boundary. Methodology. Mathematical simulation, computational experiment findings. The mathematical simulation of thermophysical processes during the dissociation of gas hydrate in a porous rock layer is presented. The case of gas hydrate dissociation in a porous rock layer, which exists in a stable state under the influence of relatively high initial temperature and pressure factors, is investigated. Numerical studies on the temperature and pressure patterns during the gas hydrate dissociation are performed. The nonstationary distribution of temperature and pressure along a porous rock layer during the dissociation of gas hydrate due to pressure drop at its boundary is presented. The advancement rate of the gas hydrate dissociation front and the change in the size of the dissociated gas hydrate area over the time are determined. originality. The algorithm is proposed for calculating the pressure and temperature fields in a porous rock layer in the case when the temperature of the stable gas hydrate is higher than its dissociation temperature. The factor that ensures the dissociation of gas hydrate is the pressure drop at the rock layer boundary. The effect of the endothermal reaction of gas hydrate dissociation on the heat exchange processes in the porous rock layer is presented. It is shown that the temperature and pressure values determining the gas hydrate dissociation point are changed as the front of the phase transition advances. Practical value. The proposed mathematical model and calculation algorithm can be used to predict the time characteristics and sizes of the gas hydrate dissociation zones around production wells.

Мета. Розробка методики дослідження та аналіз процесів тепломасообміну в гідратовміщуючому пористому шарі при падінні тиску на його границі. Методика. Математичне моделювання, обчислювальний експеримент. Результати. Представлена математична модель теплофізичних процесів при розкладенні газового гідрату в пористому шарі гірської породи. Досліджено випадок розкладення газового гідрату в пористому шарі гірської породи, що знаходиться у стабільному стані при відносно високих початкових показниках температурі й тиску. Виконані чисельні дослідження полів температури й тиску при розкладенні газового гідрату. Представлено нестаціонарний розподіл температури й тиску вздовж пористого пласта при розкладенні газового гідрату внаслідок падіння тиску на його границі. Визначена швидкість просування фронту розкладення газового гідрату та зміна розмірів області розкладеного газового гідрату переходу у часі. Наукова новизна. Запропоновано алгоритм розрахунку полів тиску й температури в пористому шарі у випадку, коли температура стабільного газового гідрату вище значення температури його дисоціації. Фактором, що забезпечує процес розкладення газового гідрату, є падіння тиску на границі породного шару. Показано вплив ендотермічної реакції дисоціації газового гідрату на процеси теплообміну в пористому шарі. Показано, що значення температури й тиску, які визначають точку розкладення газового гідрату, змінюються в міру просування фронту фазового переходу. Практична значимість. Запропоновані математична модель та алгоритм розрахунку можуть бути використані для прогнозування часових характеристик і розмірів зон розкладення газових гідратів навколо експлуатаційних свердловин.
Математичне моделювання процесів тепломасообміну при розкладенні газових гідратів у пористому середовищі
Keywords: gas hydrates dissociation; heat exchange process; endothermal reaction; hydrate dissociation; pressure drop; розкладення газових гідратів; процеси теплообміну; ендотермічна реакція; дисоціація гідрату; падіння тиску